Strategi Pembelajaran Al Qur'an yang Menyenangkan untuk Anak SD Taman Siswa Huta 1 Kecamatan Bandar, Kabupaten Simalungun - Hanum, Sri Mullatifah; Rakipah, Rakipah; Fakhita, Nurhani; Hasibuan, Ali Daud (Lembaga Yasin AlSys, 2025)
This study aims to explore enjoyable Quran learning strategies at SD Taman Siswa Huta 1, Bandar District, Simalungun Regency, North Sumatra, and identify the challenges faced by teachers in implementing these strategies. The research used a field study method with a descriptive qualitative approach, collecting data through observation, in-depth interviews with three key informants (Quran teacher, general teacher, and student affairs teacher), and relevant documentation. The main findings of this study indicate that enjoyable learning strategies can be applied through game-based approaches, visual and audio media, as well as phonetic and tajwid instruction with Islamic songs. These strategies proved effective in increasing student interest and creating a more lively classroom atmosphere. However, the main challenges faced include limited facilities, differences in students' levels of understanding, and lack of parental support in the learning process at home. This study recommends enhancing digital learning facilities and strengthening cooperation between schools and parents to support the success of enjoyable Quran learning strategies.